Cultivation, nutritional value, bioactive compounds of morels, and their health benefits: A systematic review - Li, Yitong; Chen, Hongyu; Zhang, Xi (Frontiers in Nutrition, 2023)
Morels are valuable mushrooms being used as foods and medical substances for a long history. The commonly cultivated morel species include M. eximia, M. importuna, and M. sextelata in China, M. conica and M. esculenta in the US. Morels’ nutritional profile mainly consists of carbohydrates, proteins, fatty acids, vitamins, minerals and organic acids, which are also responsible for its complex sensory attributes and health benefits. The bioactive compounds in morels including polysaccharides, phenolics, tocopherols and ergosterols contribute to the anti-oxidative abilities, anti-inflammation, immunoprotection, gut health preservation, and anti-cancer abilities. This review depicted on the cultivation of morels, major bioactive compounds of different morel species both from fruit bodies and mycelia, and their health benefits to provide a comprehensive understanding of morels and support the future research and applications of morels as high-value functional food sources.